2022
DOI: 10.1186/s12937-022-00825-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a family web-based nutrition intervention to increase fruit, vegetable, and dairy intakes: a single-blinded randomized family clustered intervention

Abstract: Background The importance of adopting healthy eating habits at a young age to prevent obesity and chronic diseases justifies the need for effective interventions. Objective This study evaluated the impact of a family web-based nutrition intervention on vegetable and fruit (V/F) and dairy product (DP) consumption, nutrient intakes, diet quality and BMI or BMI z-scores. Methods Forty-three families with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
1
3
1
Order By: Relevance
“…In contrast to what was found for fruit consumption per serving, the intake of fruit juices per day was positively related to an increase 0.27 kg/m 2 and 0.40 cm of BMI and waist circumference, respectively, for each serving of juice consumed. This finding differs from that found in other works in which the intake of natural fruit juices showed an inverse and dose-dependent relationship with BMI and waist circumference [25][26][27][28][29][30][31][32][33]. Methodological differences in the assessment of fruit juice intake may partly explain this discrepancy.…”
Section: Comparison With Other Studiescontrasting
confidence: 96%
See 2 more Smart Citations
“…In contrast to what was found for fruit consumption per serving, the intake of fruit juices per day was positively related to an increase 0.27 kg/m 2 and 0.40 cm of BMI and waist circumference, respectively, for each serving of juice consumed. This finding differs from that found in other works in which the intake of natural fruit juices showed an inverse and dose-dependent relationship with BMI and waist circumference [25][26][27][28][29][30][31][32][33]. Methodological differences in the assessment of fruit juice intake may partly explain this discrepancy.…”
Section: Comparison With Other Studiescontrasting
confidence: 96%
“…Consuming more servings of fruit per day was inversely related to BMI and waist circumference. These findings are in line with previous cross-sectional [27,28] and prospective [3,13,[27][28][29] studies. Although differences in the magnitude of the beta coefficients between fruit intake and anthropometric markers among studies exists, it should be considered that this variability may reflect the diverse nature of the population studied.…”
Section: Comparison With Other Studiessupporting
confidence: 93%
See 1 more Smart Citation
“…This result may indicate that families found it easier to increase redemption than intake, and they turned to storage-friendly options to reap the full value of the augmented CVB. Changes to the amount of the WIC-issued CVB may not alter established preferences absent further educational interventions to promote increased intakes of less familiar types of FVs [ 43 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In school-aged children, interventions taking a rather innovative approach have been conducted, such as school-based gardening, 93 gamification strategy to nutrition and physical activity, 94 or interventions delivered by class-room teachers. 95 However, only few studies conducted in school-aged children have found intervention effects (for example, other works [94][95][96] ), and the majority of studies have shown no effects of the intervention (for example, previous studies 93,[97][98][99][100][101][102][103] ).…”
Section: Main Findings From Updated Reviewmentioning
confidence: 99%